2022
DOI: 10.3390/ijerph19020766
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Plastics from WEEE: A Review of the Environmental and Human Health Challenges Associated with Brominated Flame Retardants

Abstract: Waste electrical and electronic equipment (WEEE) presents the dual characteristic of containing both hazardous substances and valuable recoverable materials. Mainly found in WEEE plastics, brominated flame retardants (BFRs) are a component of particular interest. Several actions have been taken worldwide to regulate their use and disposal, however, in countries where no regulation is in place, the recovery of highly valuable materials has promoted the development of informal treatment facilities, with serious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 47 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…Many countries, such as China, Japan, and Indonesia, have adapted annexes relating to BFR–POPs from the Stockholm Convention, however many of the signers of the agreement have yet to put legislation in place to ban these hazardous chemicals, such as the 52 African countries that have signed or Brazil, South America's leading producer of the Waste Electrical and Electronic Equipment (WEEE). [ 101 ] While the Stockholm Convention does not restrict the production of POPs, the use and recycling of materials containing POPs are meant to be regulated. [ 102 ] The European Union (EU) introduced Regulation 2019/1021 to control the restriction of POPs, set containment limits, and, most importantly, outline disposal methods for materials that contain POPs.…”
Section: Legislation Surrounding Flame‐retardant Additivesmentioning
confidence: 99%
“…Many countries, such as China, Japan, and Indonesia, have adapted annexes relating to BFR–POPs from the Stockholm Convention, however many of the signers of the agreement have yet to put legislation in place to ban these hazardous chemicals, such as the 52 African countries that have signed or Brazil, South America's leading producer of the Waste Electrical and Electronic Equipment (WEEE). [ 101 ] While the Stockholm Convention does not restrict the production of POPs, the use and recycling of materials containing POPs are meant to be regulated. [ 102 ] The European Union (EU) introduced Regulation 2019/1021 to control the restriction of POPs, set containment limits, and, most importantly, outline disposal methods for materials that contain POPs.…”
Section: Legislation Surrounding Flame‐retardant Additivesmentioning
confidence: 99%
“…Some informal disposal and handling practices of e-waste show in Figure 6. Recent studies also indicated that the workers who engaged in informal recycling had limited knowledge and awareness [53,57,58]. This exhibit as they work without using any safety dresses, or even not practising personal sanitation measures such as not washing hands before meals and not wearing clean clothes every day [47].…”
Section: Strategies To Enhance E-waste Management In South-asia Incre...mentioning
confidence: 99%
“…Regarding the plastics in EEE applications, flame retardants containing halogenated components are added to reduce its flammability but can cause difficulties in its EoL treatment [3,6]. Due to still inefficient collection and management practices of WEEE, a high proportion of this waste is illegally exported to Africa and Asia, where it is handled by informal workers under unsuitable environmental, health and safety conditions [4,7].…”
Section: Introductionmentioning
confidence: 99%